Association of Type 2 Diabetes Mellitus with Fatty Liver - Shah, Syed Umer; Hafeez, Muhammad; Naveed, Muhammad; Hussain, Altaf; Khan, Muhammad Shahid; Shahbaz, Shanzah (Pakistan Armed Forces Medical Journal, 2022)
Objective: To assess the association of fatty liver with type 2 diabetes and other socio-demographic factors among the patients at Pak Emirates military hospital Rawalpindi.Study Design: Cross-sectional analytical Study.Place and Duration of Study: Pak Emirates Military Hospital, Rawalpindi Pakistan from Aug 2019 to Jan 2020.Methodology: This study was conducted on 300 patients of type 2 diabetes mellitus reporting for a routine checkup at the medical Outpatient department. Fatty liver was diagnosed on ultrasound by a consultant radiologist.Results: Out of three hundred patients with diabetes mellitus included in the final analysis, 225(75.0%) were males, and 75(25.0%) were females. 176(58.6%) had fatty liver on ultrasound, while 124(41.4%) had no fatty liver on ultrasound examination at the time of the study. we found that increasing age, long duration of diabetes and poor control of illness had a statistically significant relationship with the presence of fatty liver among the target population (p